Acquired and hereditary bone marrow failure: A mitochondrial perspective - Nasr, Waseem; Filippi, Marie-Dominique (Frontiers in Oncology, 2022)
The disorders known as bone marrow failure syndromes (BMFS) are life-threatening disorders characterized by absence of one or more hematopoietic lineages in the peripheral blood. Myelodysplastic syndromes (MDS) are now considered BMF disorders with associated cellular dysplasia. BMFs and MDS are caused by decreased fitness of hematopoietic stem cells (HSC) and poor hematopoiesis. BMF and MDS can occur de novo or secondary to hematopoietic stress, including following bone marrow transplantation or myeloablative therapy. De novo BMF and MDS are usually associated with specific genetic mutations. Genes that are commonly mutated in BMF/MDS are in DNA repair pathways, epigenetic regulators, heme synthesis. Despite known and common gene mutations, BMF and MDS are very heterogenous in nature and non-genetic factors contribute to disease phenotype. Inflammation is commonly found in BMF and MDS, and contribute to ineffective hematopoiesis. Another common feature of BMF and MDS, albeit less known, is abnormal mitochondrial functions. Mitochondria are the power house of the cells. Beyond energy producing machinery, mitochondrial communicate with the rest of the cells via triggering stress signaling pathways and by releasing numerous metabolite intermediates. As a result, mitochondria play significant roles in chromatin regulation and innate immune signaling pathways. The main goal of this review is to investigate BMF processes, with a focus mitochondria-mediated signaling in acquired and inherited BMF.